Kolaborasi Industri dan Dunia Pendidikan dalam Penguatan Kompetensi SDM Lulusan Perguruan Tinggi - Isnawardatul Bararah (Yayasan Putroe Ceudah Aceh, 2026)
This study aims to analyze the influence of industry collaboration and the world of education on strengthening the competence of human resources of university graduates. The research is motivated by the increasing need for the world of work for graduates who have academic, professional, adaptive skills, and job readiness in accordance with industrial developments and digital transformation. This study uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The research population is 134 students of Islamic Education Management class 2022 at Ar-Raniry State Islamic University Banda Aceh, with a research sample of 97 respondents selected using random sampling techniques. The research instrument is in the form of a Likert scale questionnaire that measures the variables of industry collaboration and the world of education as well as the competence of graduate human resources. The results of the study show that the collaboration of industry and the world of education have a positive effect on the competence of graduate human resources with a path coefficient value of β = 0.270. In addition, the relationship between the two variables has proven to be significant with a p-value of 0.000 < 0.05. The results of the study also show that the collaboration of industry and the world of education have a direct effect on the competence of graduate human resources without going through a mediation variable with a determination coefficient value of R² = 0.681 which is included in the moderate category. These findings show that the synchronization of curriculum, internship programs, industry involvement in learning, soft skills development, technology support, and sustainable partnerships can improve academic competence, professional competence, job readiness, adaptability, and competitiveness of college graduates. This research contributes to strengthening the collaboration model of industry and the world of education based on the needs of the job market and the development of the quality of human resources of university graduates.